Transnational Ethnic Channels as Factors of Contagion, Internationalization, and the "Proxyfication" of Internal Conflicts: The Contrasting Cases of Amazighs and Kurds. Issue 1 (2nd January 2021) - Golubev, Denis S.
ABSTRACT: The article raises the issue of why some transnational ethnic groups (TEGs) in the Middle East and North Africa (MENA) region are more effective transmitters of conflict and instability across established borders than others. The cases involving Kurds and Amazighs present some interesting variations of agency for both groups with regard to the external expansion of internal conflicts in some of the countries of their residence. A comparative analysis of the divergent experiences of Kurds and Amazighs with respect to contagion, internationalization (mostly through intervention), and what one might term the "proxyfication" of relevant conflicts in the region reveals some underlying factors that help construct the author's main argument and working hypotheses for the large-N empirical part of this study. What emerges is strong empirical support for the proposition that four characteristics of MENA-based TEGs – namely, group discrimination, the relative size of the group, the ethnic polarization of the group's state of residence, and the group's territorial concentration – all to some extent serve as factors of external expansion of internal ethnic conflict. Out of these four features, group discrimination and the territorial concentration of the group, which are the factors about which the Kurds and Amazighs appear to differ the most, turn out to be the most reliable predictors of TEG-based conflict expansion.